1998
DOI: 10.1292/jvms.60.687
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Respiratory Function during Swimming Exercise in Thoroughbreds.

Abstract: ABSTRACT. Equine respiratory patterns during swimming were examined in five normal horses. The experiment included a preliminary warming-up stage and 6 circuits of swimming around an annular pool of a 50-meter-circumference. The horses were examined for respiratory rates, intratracheal pressures, inspiratory time (T I ), expiratory time (T E ), respiratory cycle (T; T I +T E ), heart rates, blood lactate concentrations, hematocrit and blood gases. The respiratory rates were maintained around 25/min. Blood gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 7 publications
(16 reference statements)
5
27
0
1
Order By: Relevance
“…The heart rate values of 130 -202 bpm obtained during the swimming tests were closely comparable with the 130 -210 bpm previously reported (Hobo et al 1998, Misumi et al1994aand b, Thomas et al 1980. Maximum heart rate during the swimming test in the present study (202 bpm) was lower than the average maximum heart rate of 223 bpm in Thoroughbred horses during a race (Krzywanek et al 1970).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The heart rate values of 130 -202 bpm obtained during the swimming tests were closely comparable with the 130 -210 bpm previously reported (Hobo et al 1998, Misumi et al1994aand b, Thomas et al 1980. Maximum heart rate during the swimming test in the present study (202 bpm) was lower than the average maximum heart rate of 223 bpm in Thoroughbred horses during a race (Krzywanek et al 1970).…”
Section: Discussionsupporting
confidence: 91%
“…The average plasma lactate concentration (2.3 ±1.6 mmol/L) obtained in this study is comparable with data found in earlier swimming studies (Hobo et al 1998, Gatta et al 1999. In the present study one horse had a higher plasma lactate concentration after the swimming test (6.6 mmol/L); this suggests that during swimming exercise the anaerobic contribution to the energy demands of this horse was quite significant.…”
Section: Figsupporting
confidence: 92%
“…There have been several investigations of the physiological responses of horses to swimming (Hobo et al 1998), but as with humans, it is very difficult to standardise the intensity and velocity of the movement of the horse in the pool, therefore measurements are often inaccurate.…”
Section: Assessment Of the Small Animal Patient For Hydrotherapymentioning
confidence: 99%
“…Previous studies have investigated the effectiveness of a swimming exercise test for evaluating changes in performance measures, skeletal muscle composition (Misumi et al, 1994, 1995), and respiratory function (Hobo et al, 1998). However, previous studies, have not established the physiological benefits of swim training for horses; therefore, the aim of this study was to examine the effect of swim training duration on physiological characteristics in Jeju crossbred riding horses.…”
Section: Introductionmentioning
confidence: 99%